Chapter 3 How body size became a disease A history of the body mass index and its rise to clinical importance - Flegal, Katherine (Taylor & Francis, 2022)
Taller people tend to weigh more than shorter people. This chapter will interrogate how weight varies with height. The body mass index (BMI, calculated as weight (W) divided by height (H) squared) is one way to express weight adjusted for height. It is widely used with the advantages of being technically uncomplicated, non-invasive, easy to measure and calculate. Where did it come from? How did it become the definition of a disease?